2018
DOI: 10.33095/jeas.v24i105.67
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Management Control Systems (Mcs) on Organizations Performance a Literature Review

Abstract: The impact of management control systems (MCS) on organizations performance empirical research has been the subject of numerous studies during the past decade in developed and emerging economies. In the contemporary competitive, complex and changing global business environment, firms are being challenged to adopt business models that enable them to address the strategic uncertainties and risks they face in their business environments. The main issue of this study is that management accounting researchers argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…In addition, this research study found that control system positively and significantly influenced the customer satisfaction of commercial state corporations in Kenya. The research study findings concur with the argument by Alkhafaji et al (2018) who found a strong linkage between management control systems and the performance of an organization. The research study findings also agree with the observation by Ongâand Abbey (2019), that the association between internal control systems and the quality of health service delivery was positive and significant.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, this research study found that control system positively and significantly influenced the customer satisfaction of commercial state corporations in Kenya. The research study findings concur with the argument by Alkhafaji et al (2018) who found a strong linkage between management control systems and the performance of an organization. The research study findings also agree with the observation by Ongâand Abbey (2019), that the association between internal control systems and the quality of health service delivery was positive and significant.…”
Section: Discussionsupporting
confidence: 90%
“…Centralized control significantly influences organizational performance. Alkhafaji et al(2018) assessed how control systems affected organizational performance in Malaysia and found a strong linkage between management control systems and organizational performance. In a cross-sectional study, Ongâ and Abbey (2019) examined the relationship between control systems and the quality of service delivery in the public health sector in a local government in Uganda.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The second analysis is the ''radical critique'' of appraisal. This critical management literature argues that appraisal and performance management are more covert forms of management control (Alkhafaji et al, 2018). This argues that tighter management control over employee behaviour can be achieved by the extension of appraisal to both manual and professional workers.…”
Section: Criticismmentioning
confidence: 99%
“…Begitu juga perguruan tinggi swasta di Jawa Tengah yang rata-rata belum menerapkan sistem penghargaan dan hukuman ini dengan adil dan menyeluruh. Sejalan dengan Alkhafaji et al (2018); Nguyen et al (2017) yang menyatakan bahwa dengan sistem penghargaan dan hukuman yang adil akan mendorong upaya terbaik dari para bawahan untuk meningkatkan kinerjanya. Dengan adanya keadilan prosedural maupun keadilan distribusi dalam upaya pengendalian manajemen organisasi dalam hal ini sistem Jurnal Kajian Akuntansi, Vol.…”
Section: Pembahasanunclassified